Cor Triatriatum Dexter Associated with an Ostium Primum Atrial Defect and Left-Sided Opening of the Coronary Sinus in a Stillborn Fetus - Silvia Farkašová Iannaccone; David Sedmera; Alžbeta Ginelliová; Peter Bohuš; Lucia Mistríková; Daniel Farkaš (Journal of Cardiovascular Development and Disease, 2023)
Cor triatriatum is a very rare cardiac malformation characterized by the presence of an abnormal interatrial membrane separating either the left or right atrial chamber into two compartments. It can be associated with other cardiac defects and is often symptomatic in childhood. The signs depend on the size and position of the interatrial membrane and other associated malformations. Here we report a case of right-sided cor triatriatum associated with an ostium primum-type interatrial septum defect and left-sided opening of the coronary sinus in a fetus. The cause of intrauterine death was asphyxia due to total placental abruption.